Circannual variations of water quality from springs in rural region of Eastern Herzegovina - Lolić Svjetlana; Dekić Radoslav; Janjić Nina; Ivanc Aleksandar; Erić Živojin; Savić Nebojša (Agroznanje, 2011)
Good and healthy drinking water is water with good organoleptic properties (without color, smell and taste), without the presence of substances that could affect the human health (chemically safe water) and without the presence of disease agents that could be transmitted by water (microbiologically safe water). It is imperative to supply the population with good and safe water in sufficient quantity. Investigations included seasonal analysis of physical, chemical and microbiological characteristics of water of springs Žukovik and Brestovik, the stream Mirotinj and the river Sušica. The results show that the quality of water of the springs Žukovik and Brestovik does not satisfy the prescribed values for the physical, chemical and microbiological parameters. At the same time research of the water quality of the stream Mirotinj and the river Sušica shows that their water is health safe.